Perjalanan Samuel Mengurapi Saul dan Daud Menjadi Raja Atas Israel - Grecetinovitria Merliana Butar-butar; Debora Retinawati Nababan; Nataly Hasibuan; Aberta Septia Sari Lumbanraja (Jurnal Silih Asah, 2024)
This Research Explores The Importance Of Anointing In Hebrew And Greek Traditions, As Well As The Role Of Anointing In The Old Testament Which Gave Authority And Power To Kings, Priests, And Prophets. Anointing, Which Uses Oil As A Symbol Of The Holy Spirit, Creates A Special Relationship With God And Is A Sign Of Divine Authority. This Study Highlights The Journey Of Samuel Who Was Chosen By God To Anoint Saul And David As Kings Of Israel, Showing Samuel's Obedience To God's Call As Well As The Impact Of The Anointing In Building Spiritual And Political Leadership.